The Elements Of Banyumas Traditional Historiography - Priyadi, Sugeng (Patra Widya: Seri Penerbitan Penelitian Sejarah dan Budaya., 2020)
The historiographical analysis shows that Babad Pasir and Babad Banyumas have two dominant elements, i.e. genealogy and narrative units. Both have genealogy covering (1) the ancestral genealogy, (2) the main genealogy, (3) the descendant genealogy, and (4) the branch genealogy, as the narrative units tend to dominantly reflect the relation of patron-client and the legitimation of the clan.